Therapeutics of Digestive Endoscopic Tunnel Technique - Linghu, Enqiang; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book elaborates on a whole new understanding of digestive endoscopy, the core of which is to treat quite a number of diseases using minimally invasive methods, provides the walls of the digestive tube are free of perforations. Currently, the tunnel technique has been applied in the treatment of digestive early stage carcinomas, esophageal achalasia and submucosal tumors originating from muscularis propria. And this promising technique would surely be more widely used in the future. The main contents of this book include the history of the digestive endoscopic tunnel technique, the practical anatomy involved, operation steps, indications and contraindications, complications and possible future exploration fields. This book is well suited for doctors and surgeons performing digestive endoscopic therapies. Editor Enqiang Linghu is endoscopist and professor at the Department of Gastroenterology and Hepatology, Chinese PLA General Hospital, Beijing, China.
Principles of digestive endoscopic tunnel technique -- Indications of tunnel technique -- Endoscopic Ling classification of the esophageal lumen -- Techniques in tunnel establishment -- Process of tunnel establishment and anatomic marks within the tunnel -- Tunnel technique for digestive mucosal lesions -- Tunnel technique for esophageal achalasia -- Tunnel technique for SMTs originating from muscularis propria -- Treatment$1!# (Band prevention of complications of tunnel technique -- Experimental researches of digestive endoscopic tunnel technique -- Equipments and accessories.s
Keywords: Medicine; Gastroenterology; Cancer -- Surgery; Endoscopic surgery; Medicine & Public Health; Gastroenterology; Surgical Oncology; Minimally Invasive Surgery